Keragaman Konsumsi Pangan Dan Status Gizi Remaja Putri Yang Tinggal Dikos-Kosan - Retni Retni; Mariza Arfianti (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Background: The burden of malnutrition in Indonesia is quite large, with more than a quarter of the adolescent population aged 16-18 years, 27 percent experiencing stunting and 8 percent being underweight, the prevalence of anemia in young women aged 13-18 years is 22.7 percent. The highest prevalence of chronic energy deficiency (CED) in women of childbearing age is experienced by adolescents aged 15-19 years, reaching 36.3%. Nutritional problems in adolescents have serious implications for the health of young people, affecting the well-being of current and future generations, as well as the economy and health of countries. In particular, the nutritional status of adolescent girls is closely related to pregnancy outcomes and the health and survival of mothers and children. Objective: To identify the diversity of food consumption and nutritional status of young women who live in boarding houses Methods: This study is an analytic observational study with a cross-sectional design that aims to identify the diversity of food consumption and nutritional status of female adolescents living in boarding houses. The sample in this study were young women who had just entered higher education at the age of 18-19 years, who lived in boarding houses, totaling 49 people. The diversity of food consumption was identified using the Semi Food Frequency Questionnaire (FFQ). Nutritional status was assessed based on body mass index and upper arm circumference. Results: The diversity of food consumption of respondents was low at 46.9%, the nutritional status based on BMI was mostly in the normal category, namely 71.42%, the nutritional status based on the LiLA category was lacking, namely 46.93%, there was no relationship between BMI and diversity in food consumption (P Value 0.13, but there is a significant relationship between the diversity of food consumption and LiLA (P Value 0.02). Conclusion: Diversity in food consumption is low and there are nutritional problems in young women living in boarding houses.